Prevailing non-normativities: exploring gender norms, transgressive desires and identities in literature by Muslim women writers of the subcontinent - Haque, Sumaiya Tasneem (BRAC University, 2014)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Master of Arts in English, 2014.